(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the knowledge and opinions of physiotherapists in using evidence based practice in their practice? Purpose: The purpose of this study is to describe the current evidence on evidence based practice, knowledge, skills, behaviour, and barriers by physiotherapists which could be the basis for analysis of Slovenian physiotherapists’ opinions. Method: This paper is a theoretical and includes analysis and critical review of literature published from 2000 to 2015. Searches were conducted on Springer Link, Science Direct, Pubmed, Cinahl, Embase in PEDro databases. Studies were considered for inclusion if they met four inclusion criteria phases. Results: After selection process twelve studies were included for analysis. Our review shows many difficulties that professionals have about knowledge, skills, behaviour and barriers in the implementation of evidence based practice. Organization: Results of the systematic review provide useful information for comparison the opinion and believes of Slovenian physiotherapists about evidence based practice. Society: Systematic focused analysis and synthesis of studies could be helpful for building blocks elements for evidence based practice model for Slovenian physiotherapists. Originality: Opinions and believes of Slovenian physiotherapists are not known therefore analysis of opinion and believes form physiotherapists form other countries could useful in implementation effective evidence based practice in Slovenia. Limitations/Future Research: Limitations of this systematic review could be in methodological quality and in numbers of the selected studies. Our review shows many difficulties that professionals have about knowledge, skills, behaviour and barriers the implementation of evidence based practice. The original studies do not explain likely explanations for these limitations and do not suggest any interventions for improving these problems. It is clear that more information is needed for a better understanding about evidence based practice.